2007
DOI: 10.1108/01443570710775838
|View full text |Cite
|
Sign up to set email alerts
|

Customer satisfaction and service quality in UK financial services

Abstract: This paper reports the results of a longitudinal study into the drivers of customer satisfaction in a large UK Bank. The findings confirm the significance of staff satisfaction and service quality, suggested by the service profit chain literature, but dispute that this comprises a simple linear relationship. The findings also question the pre-eminence afforded to the soft elements of the service encounter suggested by much of the Services Marketing literature. A five year study of the relationship between cust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 46 publications
3
98
0
2
Order By: Relevance
“…Establishing and maintaining a process configuration that produces effective outputs drives customer satisfaction and loyalty over time (Johnston and Clark 2005) and, therefore, leads to increased profitability (Heskett et al 1994). A longitudinal case study in the banking industry, for example, shows that process management supports enhanced service quality and increased customer satisfaction (Maddern et al 2007). Overall, empirical research has vastly supported the relationships between process design, customer satisfaction, and profitability (Ittner and Larcker 1998).…”
Section: Introductionmentioning
confidence: 96%
“…Establishing and maintaining a process configuration that produces effective outputs drives customer satisfaction and loyalty over time (Johnston and Clark 2005) and, therefore, leads to increased profitability (Heskett et al 1994). A longitudinal case study in the banking industry, for example, shows that process management supports enhanced service quality and increased customer satisfaction (Maddern et al 2007). Overall, empirical research has vastly supported the relationships between process design, customer satisfaction, and profitability (Ittner and Larcker 1998).…”
Section: Introductionmentioning
confidence: 96%
“…Consequently, while good process management is central to the performance of service organisations (Maddern et al, 2007), few empirically derived principles of process design are available to managers involved in service delivery. This may go some way towards explaining why business process design is difficult in practice with published estimates for success averaging ca.…”
Section: Process Design In the Bpm Literaturementioning
confidence: 99%
“…It has been suggested that BPM helps companies develop and sustain competitive advantage in the long run (Hung, 2006). For example, a longitudinal case study conducted by Maddern et al (2007) demonstrates that applying BPM principles contribute significantly to improving service quality and customer satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a fundamental BPM tenet is that processes should be managed from an understanding of customer needs (Smith and Fingar 2003). A practical implication of this principle is that BPM requires the management of processes on an 'end-to-end' basis, from customer initial contact to the fulfilment of customer needs (Maddern et al 2007). Such a postulate suits the service sector notion that a service process is always triggered by the customer and must provide results to a customer (Fließ and Kleinaltenkamp 2004) and, in theory, once the process is started a series of organisational resources are set in motion so that the customer gets, in the end, what he or she needs according to his or her expectation.…”
Section: The Need For a Systemic Perspectivementioning
confidence: 99%
“…By adopting BPM, companies hope to design totally customer-focused business processes, integrating all the resources needed to delight customers and eliminate inefficiencies that compromise the quality of the service (Smith and Fingar 2003). However, recent research suggests that although most companies are managing processes well within local business units, just a few are successfully managing 'end-to-end' processes across business units, from first customer contact right through the fulfilment (Maddern et al 2007). Differently from manufacturing, service processes can become invisible.…”
Section: Introductionmentioning
confidence: 99%